Strategies and evaluation underpinning the implementation of suicide prevention training: a systematic review - Adelia Khrisna Putri; Martina McGrath; Rachel Batchelor; Victoria Ross; Karolina Krysinska; Jacinta Hawgood; Kairi Kõlves; Lennart Reifels; Jane Pirkis; Karl Andriessen (BMC Public Health)
Abstract Background Suicide prevention training programs can enhance the capacity for suicide prevention by improving the attitudes and comprehension of individuals regarding suicide and increasing their skills in supporting a suicidal person. However, little is known about how training programs are implemented and how implementation is assessed. Thus, our review aims to identify the strategies and evaluation methods underpinning the implementation of suicide prevention training programs. Methods The systematic review adhered to the PRISMA guidelines and involved searches in MEDLINE, Embase, Emcare, PsycINFO, EBM Reviews, Scopus, and a forward and backward citation search following the full-text screening. Eligible studies (n = 28) reported the implementation strategy or implementation evaluation of a suicide prevention training program (PROSPERO #CRD42021288621). Results The implementation strategies varied among three categories of training programs. Gatekeeper training predominantly utilized a train-the-trainer format and collaborations with stakeholders. Professional development training focused more on establishing supportive organizational infrastructure and extended post-training supervision. School-based curriculum training programs emphasized the distribution of educational materials and role-play activities. Surveys were the primary evaluation method, often complemented by interviews, observations, progress tracking, or focus groups. Evaluations primarily assessed acceptability, fidelity, and feasibility. Conclusion While certain training categories tend to employ specific strategies and evaluation measures more frequently than others, stakeholder collaboration, assessing content relevance, and follow-up supervision could be valuable across training programs. Tailored strategies may cater for groups with varying levels of knowledge and training in suicide prevention to enhance acceptability and feasibility. Future research should evaluate approaches that facilitate adoption and sustainability of suicide prevention training programs.